2017
DOI: 10.15317/scitech.2017.67
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Formic Acid by Reactive Extraction Using an Environmentally-Friendly Solvent

Abstract: Today many carboxylic acids are recovered from biological production media and industrial wastewaters. Reactive extraction is favored over other separation methods due to its high recovery efficiency, ease of operation, low energy demand and reduced cost. However, use of toxic organic diluents in the organic phases is the main disadvantage of the method. In this study, the appropriateness of an environmentally-friendly solvent, sunflower oil (SFO) to be used as organic phase diluent during the recovery of form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 31 publications
(100 reference statements)
5
14
0
Order By: Relevance
“…Recovery of fumaric acid with the help of modified oils (made from sunflower, rice bran, & Sesame oil) was carried out in the manner as described in the section: experimental setup used and procedure.The modified oils failed to extract fumaric acid from aqueous solution.Marti [13] also reported that sunflower oil could not extract formic acid so above observation is consistent with the results cited in the literature. The TOA was used as extractant to facilitate the process of extraction of fumaric acid from aqueous solution.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Recovery of fumaric acid with the help of modified oils (made from sunflower, rice bran, & Sesame oil) was carried out in the manner as described in the section: experimental setup used and procedure.The modified oils failed to extract fumaric acid from aqueous solution.Marti [13] also reported that sunflower oil could not extract formic acid so above observation is consistent with the results cited in the literature. The TOA was used as extractant to facilitate the process of extraction of fumaric acid from aqueous solution.…”
Section: Resultssupporting
confidence: 91%
“…The values of Z decrease with the increase in % TOA and are higher for higher acid concentration. Marti [13] and H Uslu [6] also obtained similar values of Z while using natural diluents.…”
Section: Resultsmentioning
confidence: 62%
“…ese results are in agreement with the finding of Marti [34] for formic acid. Also, Marti [34] compared the results of extraction of formic acid using alamine 336 in sunflower oil with alamine octanol system.…”
Section: Effect Of Tri-n-octylamine Concentration On Loadingsupporting
confidence: 92%
“…Also, Marti [34] compared the results of extraction of formic acid using alamine 336 in sunflower oil with alamine octanol system. e values of loading ratio (Z) decrease with the increase in alamine concentration, and at higher initial concentration, often the values of Z are greater than 0.5, indicating the formation of alamine-acid aggregates [34].…”
Section: Effect Of Tri-n-octylamine Concentration On Loadingmentioning
confidence: 99%
See 1 more Smart Citation